EXPERIENCE OF USING GAME METHODS IN THE EDUCATION SYSTEM OF UZBEKISTAN - Dilorom Jalilova Jura qizi,; Suxrob Marufov Safarovich,; Mashhura Axmatqulova Xayrulla qizi, (TADQIQOTLAR, 2025)
Abstract: Research on the use of game methods in the educational process in Uzbekistan is one of the most actively developing areas of modern pedagogy. Game methods are considered as an effective tool for increasing students' cognitive activity, strengthening  their  motivation,  forming  independent  thinking  skills,  and  analyzing problem situations. This article comprehensively covers the experience of using game technologies in the education system of Uzbekistan, the innovative approaches created on their basis, the results obtained in the process of using practical examples, statistical data, and the pedagogical effectiveness of game  methods. During the research, the possibilities of applying game methods, their advantages, and existing limitations are scientifically analyzed using the example of schools, colleges, and higher educational institutions.